High attenuation areas on chest computed tomography in community-dwelling adults: the MESA study. Issue 5 (28th July 2016) - Podolanczuk, Anna J.; Oelsner, Elizabeth C.; Barr, R. Graham; Hoffman, Eric A.; Armstrong, Hilary F.; Austin, John H.M.; Basner, Robert C.; Bartels, Matthew N.; Christie, Jason D.; Enright, Paul L.; Gochuico, Bernadette R.; Hinckley Stukovsky, Karen; et al.
Evidence suggests that lung injury, inflammation and extracellular matrix remodelling precede lung fibrosis in interstitial lung disease (ILD). We examined whether a quantitative measure of increased lung attenuation on computed tomography (CT) detects lung injury, inflammation and extracellular matrix remodelling in community-dwelling adults sampled without regard to respiratory symptoms or smoking. We measured high attenuation areas (HAA; percentage of lung voxels between −600 and −250 Hounsfield Units) on cardiac CT scans of adults enrolled in the Multi-Ethnic Study of Atherosclerosis. HAA was associated with higher serum matrix metalloproteinase-7 (mean adjusted difference 6.3% per HAA doubling, 95% CI 1.3–11.5), higher interleukin-6 (mean adjusted difference 8.8%, 95% CI 4.8–13.0), lower forced vital capacity (FVC) (mean adjusted difference −82 mL, 95% CI −119–−44), lower 6-min walk distance (mean adjusted difference −40 m, 95% CI −1–−80), higher odds of interstitial lung abnormalities at 9.5 years (adjusted OR 1.95, 95% CI 1.43–2.65), and higher all cause-mortality rate over 12.2 years (HR 1.58, 95% CI 1.39–1.79). High attenuation areas are associated with biomarkers of inflammation and extracellular matrix remodelling, reduced lung function, interstitial lung abnormalities, and a higher risk of death among community-dwelling adults. Increased lung attenuation on CT may identify subclinical lung injury and inflammation in community-dwelling adults http://ow.ly/97k3300tvKX